Density of wild boar population and spread of African swine fever in the Russian Federation - O. I. Zakharova; A. A. Blokhin; N. N. Toropova; O. A. Burova; I. V. Yashin; F. I. Korennoy (Ветеринария сегодня)
African swine fever (ASF) is a transboundary viral disease affecting all species of the Suidae family. It greatly undermines global pig industry and causes a significant damage to the ecology of the wild boar (Sus scrofa) which is a natural reservoir of the virus and is an intermediate  link in the epizootic process. Depopulation of wild boars is one of the measures taken to prevent spread of African swine fever in the Russian Federation. A threshold density of the wild boar population of 0.25 boars/1000 ha (0.025 boars/km2), according to the National Plan on the ASF Eradication in the Russian Federation, was achieved by 2020 in many RF Subjects. However, further analysis of the ASF epizootic situation shows that the measure has failed to eradicate the infection completely. A regression analysis showed statistically significant positive relationship between recurrent ASF outbreaks in the wild boar population and its density in a number of model subjects (N = 6). At the same time, there is no such dependence in other model subjects (N = 3), and  ASF outbreaks were recorded in wild boars at a density significantly lower than the recommended value. A review of foreign and national scientific publications has shown that such control methods as depopulation is just one part of the whole set of measures taken to eradicate African swine fever in the wild. The measure  is effective only when 70–80%  of animals are culled in a short time, which is practically impossible due to the high costs and some peculiarities of the population control and depopulation  process. Based on the results obtained, it can be concluded that a decrease in the number of wild boars does not guarantee to stop further spread of infection in the Russian Federation and it should be considered as just one part of the whole set of measures taken together with other anti-epizootic measures to eliminate and prevent ASF.